Development of the Tablet Dosage Form Composition for the Inductor of Hepatocytes Monooxygenase System Based on 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine - A. I. Petrakov; V. V. Sheikin; S. V. Krivoshchekov; E. A. Bezverkhniaia; A. M. Guryev; M. V. Belousov (Разработка и регистрация лекарственных средств, 2023)
Introduction. Cytochromes P450 depression is the reason for the low effectiveness of etiotropic and pathogenetic therapy of hepatitis. Recent experimental and clinical studies demonstrated the need for use of inducers of hepatocytes monooxygenase system to increase the effectiveness of treatment of chronic hepatitis and cirrhosis. 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine is a promising inducer of hepatocytes monooxygenase system with detoxifying and cytoprotective activity demonstrated in models of acute hypobaric hypoxia, liver ischemia, unconjugated hyperbilirubinemia, toxic hepatitis. Development of a dosage form for 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine requires evaluation of its technological properties which was the aim of the present study.Aim. Preparation of a tablet dosage form for 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine by direct pressing.Materials and methods. The object of the study was the substance of 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine (DPDX270216001 series). Lactose monohydrate (200-559-2, LLC "Neftegazkhimkomplekt", Russia), microcrystalline cellulose (100-32-2, Silverline chemicals Ltd., India), potato starch, hydroxypropyl cellulose (ZW180113, Fengchen Group Co., Ltd., Китай), talc (LLC "Agat-Med", Russia), magnesium stearate (209-150-3, Ataman Chemicals) were used as excipients. Evaluation of the substance properties was carried according to the following indicators: appearance, loss on drying, fractional composition, flowability, bulk density, porosity, tablet compression (cohesion), ejection force of the tablet from matrix. Tablet masses were evaluated according to the following indicators: flowability, bulk density, tablet compression (cohesion), ejection force of the tablet from matrix. The tablets were obtained by the method of direct pressing. The analysis of obtained tablets were carried out according to the following parameters: average weight, crushing strength, disintegration. The tests were carried out in accordance with the Russian Federation State Pharmacopoeia.Results and discussion. The substance demonstrated poor compression (cohesion), low flowability, low bulk density and high porosity. The addition of lactose monohydrate and microcrystalline cellulose improved the cohesion (compression) parameter, but increased the ejection force of the tablet from matrix. The subsequent addition of magnesium stearate reduced the ejection force of the tablet from matrix by 5 times. The flowability of the tablet mass increased to 3,5–4,0 g/s, the disintegration time of the tablets increased (13–14 min). The introduction of 10 % disintegrators into the mold improved the disintegration rates.Conclusion. Based on the studied properties of the substance, was developed the optimal ratio of tablet mass. The possibility of obtaining a dosage form – tablets of 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine by direct pressing was show.